Influential News and Policy-making - Federico Vaccari (Fondazione Eni Enrico Mattei (FEEM), 2022)
This paper analyzes the implications of those types of interventions that affect misreporting costs. I study a model of communication between an uninformed voter and a media outlet that knows the quality of two competing candidates. The alternatives available to the voter are endogenously championed by the two candidates. I show that higher costs may lead to more misreporting and persuasion, whereas low costs result in full revelation. Yet, interventions that increase misreporting costs never directly harm the voter, but those that do so slightly can be wasteful of public resources. Regulation produced by politicians leads to suboptimal interventions.
Keywords: D72; D82; D83; L51; 330; Fake news; Misreporting; Media; Policy-making; Regulation; Disinformation